THE SPLITTING OF HEPATOCYTE GAP JUNCTIONS AND ZONULAE OCCLUDENTES WITH HYPERTONIC DISACCHARIDES - Goodenough, Daniel A. (The Rockefeller University Press, 1974)
Mouse livers were perfused in situ through the portal vein with the disaccharides sucrose, lactose, maltose, and cellobiose in hypertonic concentrations (0.5 M). This treatment resulted in plasmolysis of the hepatocytes and splitting of the gap junctions and zonulae occludentes. The junctions split symmetrically, leaving a half-junction on each of the two separated cells. The process of junction splitting is followed using the freeze-fracture technique, since the junctional membranes are indistinguishable from the nonjunctional membranes in thin sections once the splitting occurs. The split junctions are also studied using the freeze-etch technique, allowing a view of the gap junction extracellular surface normally sequestered within the 2-nm "gap." The monosaccharides sorbitol and mannitol did not split the junctions during the times studied (2 min), but substitution of the chloride ion with propionate in the perfusion mixture did result in junction splitting. An envelope of morphologically distinct particles surrounding freeze-fractured gap junctions is also described.